Wage Differences Between Immigrants and Natives in Austria: The Role of Literacy Skills - Michael Christl; Monika Köppl-Turyna; Philiipp Gnan (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper analyzes wage differences between natives and immigrants in Austria. First, we show that for both groups, literacy skills are an important determinant of the hourly wage. In the second step, we show that differences in proficiency with respect to literacy can explain more than three log points of the total wage gap of 9.7 log points between natives and immigrants. When adding literacy skills to the wage decomposition, the discriminatory part vanishes completely, suggesting that the wage difference between immigrants and natives in Austria can be to a large extent explained. Furthermore, we account for a possible sample selection bias. After controlling for literacy skills, the unexplained part of the gap becomes statistically insignificant. The importance of literacy skills in explaining wage differences between natives and immigrants is robust across several sensitivity tests.
Keywords: J71; J15; 330; wage; decomposition; gap; immigrants; natives; Austria